Fixed and mobile telephones in WAEMU countries: complementary or substitute services? - CHABOSSOU, AUGUSTIN FOSTER COMLAN (My University, 2015)
The observation of the joint evolution of fixed and mobile phones penetration in West African Economic Monetary Union countries suggests that the demand of the two services does not develop at the same rate with increasing difference in favor of the mobile phone. This article is dedicated to relationship between fixed and mobile phone services. It tests empirically the existence of relations of complementarity and substituality between these two types of services in the West African Economic Monetary Union countries over the period 1997 to 2010. It is clear that in these countries, mobile phone is a fixed phone substitute, although the extent of this relationship of substitution is relatively low. Nevertheless, the role that the fixed phone is required to play in these countries for ICT services development must push the authorities to consider measures to improve the fixed phone penetration rate.
Keywords: Telephone substituable panel data WAEMU